Perancangan Aplikasi Orientasi Mahasiswa Baru Berbasis Android dengan Laravel RESTful API dan Lean Touch - Tan, Robby; Wijanto, Maresha Caroline; Lieshiana, Celine (Maranatha University Press, 2023)
The new student orientation is a period where new students adjust and become familiar with the environment and activities at the university. During the COVID-19 pandemic, the orientation activity changed from campus activities to virtual meetings. Even though the orientations held back on campus, the problems persist. These problems are communication or students' lack of alertness when paying attention to announcements or activities. The solution is to create an Android application to assist the orientation process. The application uses the Laravel Representational State Transfer (RESTful) Application Programming Interface (API) to communicate between the application and the database. Android users are divided into administrators, lecturers or committees, and students. This application uses markerless augmented reality which was created using Unity's Lean Touch library to show laboratory maps. Another feature of the application is a quiz. This feature is used to confirm given material or activities. Surveys given to the committee, lecturers, and students show that the application can support new student orientation activities.